2013
DOI: 10.1016/j.vaccine.2013.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety assessment of live attenuated tetravalent dengue vaccines: Deliberations from a WHO technical consultation

Abstract: Dengue is a rapidly growing public health threat with approximately 2.5 billion people estimated to be at risk. Several vaccine candidates are at various stages of pre-clinical and clinical development. Thus far, live dengue vaccine candidates have been administered to several thousands of volunteers and were well-tolerated, with minimal short-term safety effects reported in Phase I and Phase II clinical trials. Based on the natural history of dengue, a theoretical possibility of an increased risk of severe de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Specifically, due to the important serological prevalence, the evidence of ongoing transmission, the current re-emergence of other arboviruses, and other demographic characteristics of the study population, the introduction of dengue vaccine, along with a structured vector control program, could be considered when formulating disease control strategies. Secondly, for the developers of new dengue vaccines currently in the pipeline, this study provides evidence of the relative heterogeneity that can be observed in endemic areas such as Colombia and also shows the existing heterotypic response rates, which present a challenge that must be addressed adequately by the new vaccine candidates 17, 18, 19, 21, 22, 28, 29, 30, 33, 40, 41, 42. Overall, this study contributes to a better understanding of dengue in Medellin, Colombia, and in other Latin American settings with similar characteristics (i.e., low socioeconomic urban and peri-urban areas with intermediate to high prevalence and areas endemic for dengue).…”
Section: Discussionmentioning
confidence: 85%
“…Specifically, due to the important serological prevalence, the evidence of ongoing transmission, the current re-emergence of other arboviruses, and other demographic characteristics of the study population, the introduction of dengue vaccine, along with a structured vector control program, could be considered when formulating disease control strategies. Secondly, for the developers of new dengue vaccines currently in the pipeline, this study provides evidence of the relative heterogeneity that can be observed in endemic areas such as Colombia and also shows the existing heterotypic response rates, which present a challenge that must be addressed adequately by the new vaccine candidates 17, 18, 19, 21, 22, 28, 29, 30, 33, 40, 41, 42. Overall, this study contributes to a better understanding of dengue in Medellin, Colombia, and in other Latin American settings with similar characteristics (i.e., low socioeconomic urban and peri-urban areas with intermediate to high prevalence and areas endemic for dengue).…”
Section: Discussionmentioning
confidence: 85%
“…35,38,39,43,44,49,50 These investigators have assessed tetravalent combinations of these recombinant viruses by mixing monovalent vaccines at the clinical site. 40 A prototype monovalent DNA vaccine has been assessed in a phase 1 clinical trial. 46 …”
Section: Resultsmentioning
confidence: 99%
“…The presence of four antigenically distinct dengue viruses (DENVs) has complicated vaccine development. [2][3][4] Furthermore, the lack of an animal model that recapitulates the clinical features observed in human infections has limited our understanding of the mechanisms underlying severe dengue pathogenesis. 5 Consequently, detailed clinical, virologic, and serologic characterization of dengue patients remains a valuable resource in providing insights into possible mechanisms that drive pathologic processes.…”
Section: Introductionmentioning
confidence: 99%